The Effect of Tax Planning, Profitability and Tax Avoidance on Firm Value in Plantation Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period: Pengaruh Tax Planning, Profitabilitas Dan Tax Avoidance Terhadap Firm Value Pada Perusahaan Perkebunan Yang Terdaftar Di BEI Periode 2017-2019 - Ayu, Yullinda Novita; Ernandi , Herman (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the effect of tax planning, profitability and tax avoidance on firm value in plantation companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 13 plantation companies listed on the IDX in the 2017-2019 period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that Tax Planning Affects Firm Value, Profitability Affects Firm Value, Tax Avoidance Affects Firm Value, Tax Planning Affects Leverage, Profitability Affects Leverage, Tax Avoidance Affects Leverage